Efeito do diuron sôbre o poder nitrificante de dois solos do estado de São Paulo (nota prévia) - Kuramoto, M.; Haag, H.P.; Sarruge, J.R. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1970)
The authors related in this short communication the effect of several doses of diuron (0.2 - 0.8 mg of p.a.) on the nitrification capacity of two soils, serie "Luiz de Queiroz" and arenito de Botucatu. Analyses were run during four weeks for N-total, N-NH3 and for NO2 + NO3. The results showed that diuron had no effect on the nitrification capacity on both soils.